2013
DOI: 10.1007/s12046-013-0139-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent development of cellular manufacturing systems

Abstract: Cellular manufacturing system has been proved a vital approach for batch and job shop production systems. Group technology has been an essential tool for developing a cellular manufacturing system. The paper aims to discuss various cell formation techniques and highlights the significant research work done in past over the years and attempts to points out the gap in research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…O quadro 7 apresenta a lista completa de referências que abordam os parâmetros citados. Os tempos padrões definidos a priori são observados na prática nos processos que constituem a célula (PEINADO;GRAEML, 2007) O layout projetado para a célula demonstrase adequado para diferentes ciclos produtivos desenvolvidos pelos colaboradores (AALAEI;DAVOUDPOUR, 2016;ARORA;HALEEM;SINGH, 2013;CHANG;WU;WU, 2013;DEEP;SINGH, 2015;BLACK, 2007;METTERNICH;BECHTLOFF;SEIFERMANN, 2013;MOYANO-FUENTES;SACRISTÁN-DÍAZ, 2012;PAPAIOANNOU;WILSON, 2010;RAFIEE et al, 2011;RAMINFAR et al, 2013;RIBEIRO, 2011;TANIMIZU;ISHII;YOKOTANI, 2014) Os processos mais críticos da célula (operações restritivas) são conhecidos e constantemente gerenciados (BROWN, 2015;ERENAY et al, 2015;PEINADO;GRAEML, 2007) Quadro 7 -Parâmetros para o grupo "Configuração da célula" (conclusão)…”
Section: Parâmetros Referênciasunclassified
“…O quadro 7 apresenta a lista completa de referências que abordam os parâmetros citados. Os tempos padrões definidos a priori são observados na prática nos processos que constituem a célula (PEINADO;GRAEML, 2007) O layout projetado para a célula demonstrase adequado para diferentes ciclos produtivos desenvolvidos pelos colaboradores (AALAEI;DAVOUDPOUR, 2016;ARORA;HALEEM;SINGH, 2013;CHANG;WU;WU, 2013;DEEP;SINGH, 2015;BLACK, 2007;METTERNICH;BECHTLOFF;SEIFERMANN, 2013;MOYANO-FUENTES;SACRISTÁN-DÍAZ, 2012;PAPAIOANNOU;WILSON, 2010;RAFIEE et al, 2011;RAMINFAR et al, 2013;RIBEIRO, 2011;TANIMIZU;ISHII;YOKOTANI, 2014) Os processos mais críticos da célula (operações restritivas) são conhecidos e constantemente gerenciados (BROWN, 2015;ERENAY et al, 2015;PEINADO;GRAEML, 2007) Quadro 7 -Parâmetros para o grupo "Configuração da célula" (conclusão)…”
Section: Parâmetros Referênciasunclassified
“…The techniques and algorithms so far used for implementing CMS include Machine component group analaysis,Similartity coefficient based approaches, GA based approaches, Mathematical programming based approaches, Goal programming, Dynamic programming, Heuristic based approaches, Fuzzy clustering and AI Approaches. The paper has concluded that out of all these approaches GA based approaches are the best for CMS [9]. GA tries to imitate the natural progressions and creates a wide-ranging purpose optimization system [6].…”
Section: Cfp Design Techniquesmentioning
confidence: 99%
“…Reference [9] has pointed out the gap in research. Most of the papers published so far has paid little attention towards production planning (part scheduling and processing times) while designing CF for CMS.Based on above review, the proposed model is a novel approach to finish the gap which is still there in research.CFP will be optimized using Part Sequence, Machine Sequence and Processing times.…”
Section: Research Gap Of Cfpmentioning
confidence: 99%
“…The application of this GT is cellular manufacturing (CM) system. This system is a well built method for getting better operations in the batch manufacturing (Arora et al, 2013). The improvement of a CM system is based on the planned setup framework, implemented study of the presented system, creating elevated assembly and operational decisions, allocating worker, equipment and parts to the cells, adapting the innovative methods and assessing and developing the design (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%